MASKULINISASI IKAN NILA (Oreochromis niloticus) DENGAN MENGGUNAKAN LARUTAN MADU (Apis mellifera linneus) - Verdian, Aldi Huda; Febriani, Dian; Pamungkassari , Agustina Tri (Jurnal Perikanan Terapan, 2023)
Male tilapia is preferred by cultivators because it has a higher growth speed or matures quickly (sexual maturity) than female tilapia. Efforts need to be made to increase the production of tilapia by applying masculinization to increase the production of male tilapia. Masculinization activities can be carried out using the hormone 17α-Methyltestoteron. However, the use of these hormones usually leaves a carcinogenic residue which not only does not meet food safety requirements but also endangers consumers. Efforts to masculinize can be done by immersing the larvae in a water solution of honey. Honey contains chrysin which acts as an aromatase inhibitor resulting in increased hormone production and male traits become dominant. The purpose of this activity is to determine the male sex ratio from immersing tilapia larvae in honey solution. The larvae used were 7 days old, then soaking was carried out for 20 hours using honey with a concentration of 15 ml/L capable of producing 76% male seeds.